PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP PENTINGNYA MENJAGA PELESTARIAN LINGKUNGAN DI BERINGIN - Fatma Khuzaimah, Dewi; Wilson Sitopu, Joni; Rosenta Purba, Ika (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to determine the influence of Instagram on environmental conservation in Beringin. The author conducted observations in Beringin and observed that many individuals and communities still lack concern for environmental conservation. The approach used in this study was quantitative, using data collection methods such as distributing questionnaires to 100 Instagram users in Beringin. Based on the research results, through simultaneous testing, it was shown that the social media variable (X) influences environmental conservation (Y) in Beringin. The calculated f value (90.363) > f table (4.00) with a significance level of 0.001, and the adjusted R Square value of 0.474, or 47%. This means that the influence of social media on environmental conservation is 47%. The remaining 53% is attributed to other variables not examined in this study, such as environmental impact, environmental pollution, and social sanctions.